OBTAINING AND IMMUNOCHEMICAL CHARACTERIZATION OF MONOCLONAL ANTIBODIES TO X-VIRUS OF POTATO - Eskendirova, S.Z.; Sarina, N. I.; Manat, Y. (Eurasian Journal of Applied Biotechnology, 2014)
Modern potato seed multiplication systems on the virus-free basis provide a diagnostic control of viral infection at different stages of seed multiplication process to ensure the timely removal of infected planting material batches. Therefore, mass diagnosis of viral diseases is a key element for pest monitoring and plant breeding, for certification of planting material and quarantine measures. Enzyme-linked immunosorbent assay is currently the most common and widely used method of analysis of plant material for diagnosis and identification of pathogens. As the main immunoreagent in a solid phase of enzyme-linked immunosorbent assay there are used polyclonal antisera obtained by means of rabbits immunization using purified viral preparations. However, a serious problem in the application of antisera for identification and quantification of antigens in different areas of research is caused by reproducibility, non-specific binding and cross-reactivity of antibodies. Currently, monoclonal antibodies are used as immunoreagents in diagnostics of many viral and bacterial diseases of plants. Monoclonal antibodies significantly prevail over polyclonal antiserum in the means of specificity and sensitivity of pathogen detection in biological liquids. The method of hybridoma technology has been used to produce strains of the cultured hybrid cells that sustainably produce high-affinity monoclonal antibodies to the purified preparation of potato X-virus. The results of immunochemical characteristics of monoclonal antibodies show specificity to the epitope of the capsid protein of potato X-virus, which leads to possibility of their use as a highly sensitive and specific immunoreagents for development of diagnostic test systems.